Pengaruh Senam Hamil dengan Pemberian Aromatherapi Citrus Terhadap Penurunan Nyeri Punggung pada Ibu Hamil - Voni Ayu Kuswati; Mudy Oktiningrum; Nella Vallen Ika Puspita (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Lower back pain in pregnant women is caused by hormonal changes that loosen joints in the back of the pelvis, a lack of muscle in the abdomen, and reduced blood flow. Prenatal exercise in conjunction with citrus aromatherapy is a non-pharmacological treatment option for pregnant women to alleviate back pain. Objective: This research determined whether providing pregnancy exercises combined with citrus aromatherapy at Indri Sujarwo Midwifery Clinician Demak could relieve back pain in pregnant women. Method: This quantitative research applied a quasi-experimental design, utilizing a pretest and posttest framework. This study involved 44 respondents, who were pregnant women in their second and third trimesters and collected data through purposive sampling. The observation sheet and the NRS checklist served as the measuring instruments. Results: This study showed a p-value of 0.000 (<0.05). The study's findings denied Ho and accepted Ha, indicating the capability of pregnancy exercise and citrus aromatherapy to relieve back pain in pregnant women in their second and third trimesters. Conclusion: Pregnancy exercise, combined with citrus aromatherapy, has effects, four times higher, on relieving back pain for pregnant women, making this combination a viable alternative for pregnant women experiencing lower back painleaves (Piper ornatum) against vaginal discharge.